Minority Public Shareholders in China's Concentrated Capital Markets – A New Paradigm? - Ozery, Tamar Groswald (Columbia Journal of Asian Law, 2016)
This article provides a detailed analysis of the role of public shareholders in firm monitoring and corporate governance in one of the world's most concentrated ownership environments-China's controlled capital markets. It moves beyond the existing literature to explore in a comparative fashion innovative and sometimes idiosyncratic ways by which public shareholders can be involved in firm monitoring and corporate governance. In so doing, this article sheds new light on the global shift in the role of public shareholders towards greater empowerment and governance participation. Contributing to comparative corporate governance literature, this article offers a new analysis of current and prospective developments in the Chinese market, which is of particular importance globally as this market becomes increasingly central to the world economy.